METHODOLOGY FOR DETERMINING ACCESS TO MICRO ENTERPRISE CREDIT - Mesén Vargas, Juliana (2012)
In this paper, a methodology is developed to identify those characteristics of micro-enterprises and micro-entrepreneurs related to access to commercial credit. This methodology is applied, for illustrative purposes, to a sample of 401 micro-enterprises and micro-entrepreneurs in Costa Rica. Although the main purpose of this paper is to present the methodology rather than commenting on the results of its application, the following results should be highlighted: on average, men have more access to credit, while the levels of education and age have no significant influence on access.